RESILIENCE AND HEALTHY LIFESTYLES IN THE POPULATION OF NURSES, NURSING STUDENTS AND ADMINISTRATIVE WORKERS - Despotović, Milena; Ignjatović-Ristić, Dragana; Bankovic, Dragic; Despotovic, Mile; Zlatanovic, Milena; Jovic, Jelena (Medicinski časopis, 2025)
Aim: The aim of this study is to determine whether resilience is associated with healthy lifestyles, defines as physical activity, dietary habits and proper sleep, in a population of nurses, students and administrative workers. Materials and methods: The study included a total of 290 respondents: 149 nurses, 71 clerks and 70 nursing students, from six different cities in the territory of Serbia, during the year 2022. To assess resilience, we used Brief Resilience Scale (BRS). In order to examine the influence of healthy lifestyles, we asked respondents to fill out a questionnaire which included general questionnaire about socio-demographic and lifestyle characteristics, International Physical Activity Questionnaire (IPAQ) and Mediterranean Diet Adherence Screener (MEDAS). Results: People who predominantly use olive oil in their diet as a main culinary fat are more resilient that those who do not use it (r = 0.024). There is no statistically significant difference between resilience and parameters of physical activity. Resilience is associated with sleep problems, optimism and place of living. Conclusion: The results of our study represent an important starting point for establishing strategies for building resilience, especially in the population of healthcare workers, considering that the majority of our sample consists of nurses. Such results take on a new dimension in times of major social global changes (recent coronavirus pandemic, wars), which result in the overloading of national health systems.
Keywords: resilience, lifestyle, physical activity, dietary habits